Evaluating the Health and Environmental Consequences of Sulphur-Related Diesel Emissions (Journal of Science and Technology, 2024)
Sulphur content is one of the most important fuel parameters affecting exhaust emissions from vehicles. Sulphur is a direct pollutant that can combine with other atmospheric elements to form compounds that contribute to global warming; hence minimising its quantity in fuels is essential. Standards have been set globally to regulate the sulphur content of diesel fuels. This research undertakes a comparative analysis of the sulphur content in fuel samples, randomly collected from five different fuel station brands. The sulphur content of diesel was analysed with sulphur analyser Hitachi LAB X-5000 following the ASTM D 4294-16 test method which is deemed simple. In the Kumasi Metropolis, the mean sulphur concentration in diesel was considerably elevated (ranging from 60 – 258 parts per million (ppm)) in comparison to the global standard of 50 ppm. From the analysis, the sulphur levels were in the order: Brand A< Brand C < Brand D < Brand E < Brand B. An assessment of the impact of sulphur emissions (from cradle to gate) on health, the ecosystem, and climate change was done using SimaPro software (v9.4.0.2). The results revealed the detrimental effects of the emissions, particularly when using fuels sourced from Brand B. Therefore, it is essential to enforce measures that ensure the imported and consumed diesel in the metropolis aligns with the stipulated regulations. This will mitigate potential health risks and environmental damage that may ensue from escalated sulphur emissions. Random checks on diesel quality at retail outlets are recommended to ensure compliance with set regulations.